The Mediating Role of Information Technology between Digital Marketing and Firm Performance in Jordanian Small and Medium Enterprises - Al-Husban, Hammadallah (Journal of Management World, 2025)
This article presents a conceptual model that explores the interrelationships among digital marketing (DM), firm performance (FP), and information technology (IT) in Jordanian small and medium-sized enterprises (SMEs). Furthermore, it examines the mediator role of IT in the link between DM and FP. The validation of the conceptual model was performed utilizing IBM SPSS version 22, pursued by confirmatory factor analysis and structural equation modeling with IBM SPSS AMOS version 24. The findings revealed a significant positive relationship between digital marketing (DM) and firm performance (FP), with information technology (IT) serving as a partial mediator in the relationship between DM and FP. Furthermore, the overall impact of the dimensions of digital marketing on firm performance was assessed to be 95.92%.